Late adoption: psychologists' perception of challenges in the process of adopting older children (Research, Society and Development, 2023)
Since 1828, when the first adoption legislation appeared in Brazil, there have been reformulations in the laws aiming to guarantee the rights of children and adolescents awaiting a foster home. Currently, many families are candidates for adoption, however, the minority chooses to adopt children over the age of two, believing that they have greater difficulty adapting. As a result, there is an increase in the waiting list and the feeling of hopelessness of children and adolescents who are waiting for a new home in the host institutions. The objective of this study was to understand the perception of psychologists who work in the process of adopting older children and the factors that favor their return to foster homes. A qualitative research was carried out, with the participation of five psychologists who work in foster homes. A sociodemographic questionnaire and a semi-structured interview were used for data collection. The results were analyzed using categorical content analysis, and concluded that: (a) the unpreparedness of applicants for adoption can contribute to returns, (b) the wait and fear of being abandoned experienced by the child can trigger damage, ( c) children returned to institutions suffer emotional and cognitive damage (d) reception, affective bond and alignment of expectations of suitors can contribute to the success of adoption and (e) the challenges of psychologists are to guide suitors and help children to deal with the feelings of hopelessness that arise in the process. Concluding the importance of the professional in the healthy adoption process.